Detailed immunophenotyping of B‐cell precursors in regenerating bone marrow of acute lymphoblastic leukaemia patients: implications for minimal residual disease detection. (17th April 2017) - Theunissen, Prisca M. J.; Sedek, Lukasz; De Haas, Valerie; Szczepanski, Tomasz; Van Der Sluijs, Alita; Mejstrikova, Ester; Nováková, Michaela; Kalina, Tomas; Lecrevisse, Quentin; Orfao, Alberto; Lankester, Arjan C.; van Dongen, Jacques J. M.; et al.
Summary: Flow cytometric detection of minimal residual disease (MRD) in children with B‐cell precursor acute lymphoblastic leukaemia (BCP‐ALL) requires immunophenotypic discrimination between residual leukaemic cells and B‐cell precursors (BCPs) which regenerate during therapy intervals. In this study, EuroFlow‐based 8‐colour flow cytometry and innovative analysis tools were used to first characterize the immunophenotypic maturation of normal BCPs in bone marrow (BM) from healthy children, resulting in a continuous multiparametric pathway including transition stages. This pathway was subsequently used as a reference to characterize the immunophenotypic maturation of regenerating BCPs in BM from children treated for BCP‐ALL. We identified pre‐B‐I cells that expressed low or dim CD34 levels, in contrast to the classical CD34 high pre‐B‐I cell immunophenotype. These CD34 −dim pre‐B‐I cells were relatively abundant in regenerating BM (11–85% within pre‐B‐I subset), while hardly present in healthy control BM (9–13% within pre‐B‐I subset; P  =   0·0037). Furthermore, we showed that some of the BCP‐ALL diagnosis immunophenotypes (23%) overlapped with CD34 −dim pre‐B‐I cells. Our results indicate that newly identified CD34 −dim pre‐B‐I cells can be mistaken for residual BCP‐ALL cells, potentially resulting in false‐positive MRD outcomes. Therefore, regenerating BM, in which CD34 −dim pre‐B‐I cells are relatively abundant, should be used as reference frame in flow cytometric MRD measurements.